The impact of risk management, financial performance and executive remuneration on sustainable growth planning of SMEs in the Visegrad four countries - Belas, Jaroslav; Slepecky, Jaroslav; Nagy, Marek; Smrčka, Luboš (Transformations In Business & Economics, 2026)
Sustainability in the small and medium-sized enterprises (SMEs) is a topic that resonates strongly in the scientific environment. It is a response to phenomena and processes that are becoming an increasingly pressing issue in the socio-economic system of countries around the world. This study aims to identify the significant aspects in the field of enterprise risk management, financial performance, and manegerial renumeration in the SME sector, and to quantify their impact on sustainable growth planning. Extensive empirical research was conducted in 2025, surveying 1,549 respondents from the Visegrad Four countries. The results showed that all the independent variables defined in the areas of risk management, performance, and managerial remuneration have a significant impact on the positive perception of sustainable growth in the SME sector. The mean values of the respondents’ answers indicate a positive trend, as the positive evaluations of the defined attitudes, which were formulated as statements or independent variables, prevail in the assessed sample. The highest level of agreement was found for the statement that firms comply with financial reporting standards and regulations. This is followed by the importance of having strategic documents and good current financial position of the firm. Strategy and financial performance management, managerial remuneration, and proper business risk management were observed to have the most significant influence on SMEs’ sustainable growth planning. The presented results can not only enrich the theoretical field, but can also be useful for the management system of SMEs.